Men Are from Mars, Idiopathic Intracranial Hypertension Is from Venous: The Role of Venous Sinus Stenosis and Stenting in Idiopathic Intracranial Hypertension - Dinkin, Marc; Oliveira, Cristiano (Seminars in Neurology, 2019)
Idiopathic intracranial hypertension (IIH), also known as pseudotumor cerebri, is a disease primarily affecting obese women of child-bearing age, typically presenting with positional headaches, diplopia from abducens nerve palsies, pulse-synchronous tinnitus, and visual disturbances related to papilledema, including transient visual obscurations, blurry vision, and visual field defects. Controversy remains regarding the pathophysiology of IIH. Elevated intracranial pressure in IIH is thought to be the result of a dysregulation of cerebrospinal fluid (CSF) dynamics, through excessive secretion, reduced drainage, or both. Passive CSF drainage through the arachnoid granulations depends on a pressure gradient between the subarachnoid space and the cerebral venous system, such that elevations in cerebral venous pressure lead to impaired CSF drainage. Dural venous sinus stenosis (DVSS) at the junction of the transverse and sigmoid sinuses, leading to local venous hypertension and a secondary reduction in CSF drainage through the arachnoid granulations, is increasingly recognized as an important component of the pathophysiology of IIH. A growing number of studies have demonstrated a role for stenting of DVSS as an alternative to CSF shunting and optic nerve sheath fenestration in medically refractory IIH patients with vision loss or debilitating symptoms.
Keywords: idiopathic intracranial hypertension; venous sinus stenosis; dural venous sinus stenosis; venous sinus stenting